Pengaruh Kecerdasan Spiritual Terhadap Coping Mechanism Siswa - Sari, Putri Amanda; YM, Khairuddin; Syarifah, Syarifah (An-Nuha, 2025)
This study aims to determine the effect of spiritual intelligence on coping mechanisms of class XI students of Madrasah Aliyah Negeri 2 Langkat. This study uses a quantitative approach with an explanatory-research method. The population of the study was all class XI students of Madrasah Aliyah Negeri 2 Langkat, while the sample of the study was 104 students from class XI MIPA-1, XI IIS-1, and XI IIK-2. Data were collected through a questionnaire on spiritual intelligence and coping mechanisms, then analyzed with simple regression analysis to see the relationship between the two variables. The results showed that students' spiritual intelligence was in the medium category with a frequency of 80 (76.9%). The students' coping mechanisms are also in the moderate category with a frequency of 80 (76.9%), Based on results of a simple linier regression, the t-test was 8964 with a p-value 0f 0.000 < 0,05. It can be concluded that spiritual intelligence has a significant and positive effect on the coping mechanism of the students of class XI of Madrasah Aliyah Negeri 2 Langkat Further analysis shows the influence of spiritual intelligence on coping mechanisms with a contribution of 44.1%. These result suggest that students with higher spiritual intelligence tend to apply more adaptive cooing strategies in dealing with academic and social stressors.